Nafkah Istri Terhadap Suami Disabilitas Perspektif Hukum Islam - Arief Hanif, Hamdan (Qanun: Jurnal Hukum Keluarga Islam, 2023)
This research is motivated by the reality of the life of a husband who has a disability so that there is a limitation in the husband's role, one of which is in earning a material living so that the wife must work in order to meet the family's economic needs. The problem formulation that will be developed is about the law regarding working wives and its relevance to family support obligations. Analyze the legal basis for husbands with disabilities in relation to their obligation to provide support for their families. The aim is to know the law regarding providing family support by a wife and providing support by a husband with a disability. This research use desciptive qualitative approach. The data collection methods used by researchers are: first, documentation, which in this case is theories in fiqh, the Koran and Hadith. and the second is to conduct interview sessions with disabled families who meet the author's criteria. The data analysis technique used is content analysis, namely research that seeks the relevance of scientific theory to the content of interview information. Based on the results of this research, interviews with disabled families and literature review of several theories of fiqh, al-Qur'an and Hadith. That a wife is allowed to provide maintenance to a husband. regardless of the husband's disability, this law is general so it can be carried out by other families. From the results of the analysis, the nature of the income provided by the wife remains a side or additional income. It is not the main income, so the husband is still obliged to provide the main income. there is no reason to cancel it. Because in Islamic law, providing maintenance to a wife does not have a minimum limit, so it does not burden a husband even if he is disabled.